2017
DOI: 10.2209/tdcpublication.2016-0044
|View full text |Cite
|
Sign up to set email alerts
|

Number of Non-vital Teeth as Indicator of Tooth Loss during 10-year Maintenance: A Retrospective Study

Abstract: The purpose of this study was to investigate whether number of non-vital teeth was an indicator of tooth loss during maintenance. Thirty-three general practitioners provided data on 321 patients undergoing maintenance over 10 years. The number of present teeth (PT), smoking status, level of bone loss, number of non-vital teeth, and reason for tooth loss during that period were investigated. Multiple logistic regression was performed to identify whether the number of non-vital teeth was associated with tooth lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…33 One study showed that as the number of non-vital teeth increased, TL due to root fractures and caries increased. 34 Therefore, a decrease in the number of non-vital teeth may reduce TL due to caries, periodontal disease, and root fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 One study showed that as the number of non-vital teeth increased, TL due to root fractures and caries increased. 34 Therefore, a decrease in the number of non-vital teeth may reduce TL due to caries, periodontal disease, and root fractures.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Various factors, such as age, smoking, diabetes mellitus (DM), and others, are also related to TL, and the risk of TL increases with the presence of additional non-vital teeth (those that have undergone root canal treatment). 30,[32][33][34] Despite reports that various factors affect TL, many of these studies were conducted under special circumstances, such as at a university hospital or within a specialist clinic, where patient demographics were limited. Additionally, few studies on the risk factors for TL have utilized large sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…A presença de dentes vem sendo usada como indicador de saúde bucal, sendo que manter 20 dentes permanentes em função resguarda as condições funcional, estética e fonética, ao longo da vida (Suzuki et al, 2017). Indivíduos que não apresentam essa condição podem sofrer problemas mastigatórios, restrição de alimentos e ingestão de nutrientes inadequados (Ervin, Dye, 2007, Sheiham et al, 1999.…”
unclassified
“…PERDA DENTÁRIAO número de dentes presentes é usado como indicador de saúde bucal. Um dos objetivos da Organização Mundial de Saúde (OMS) para o Ano 2000 foi a retenção de dentição funcional, estética e natural de 20 dentes sem próteses ao longo da vida como objetivo importante da saúde bucal(Suzuki et al, 2017).A perda dentária é um dos principais problemas bucais, classificada entre as cem condições de saúde que mais afetam a população mundial, devido à sua alta prevalência, aos danos estéticos, funcionais, psicológicos e sociais que acarreta ao individuo (Barbato et al, 2007; De Marchi et al, 2012; Sanders et al, 2007; Silva-Junior, Batista, Sousa, 2017). Apesar das melhorias em conscientização e tratamento em todo o mundo, a perda dentária pode prejudicar não só a mastigação, mas também a autoestima e as interações sociais devido aos seus efeitos sobre a aparência, a capacidade de conversar e a vontade de sorrir.…”
unclassified
See 1 more Smart Citation